Hubungan Pengetahuan dan Sikap Ibu Hamil tentang Tanda Bahaya Kehamilan Terhadap Pemanfaatan Buku Kia di RSUD S.K.Lerik Kota Kupang - Jeane Herlophina Therik; Ni Made Ayu Yulia Raswati Teja; Putu Ayu Ratna Darmayanti (Universitas Malahayati Lampung, 2026)
ABSTRACT Complications during pregnancy can be prevented by recognizing danger signs. One way to recognize danger signs is by using the KIA (Child Health and Child Health) book. Poor knowledge of danger signs among pregnant women can lead to increased maternal mortality rates. To determine the correlation between knowledge and attitude of pregnant women about pregnancy danger signs towards the use of Maternal and Child Health (KIA) book in the Obstetrics and Gynecology Polyclinic at S.K.Lerik General Hospital, Kupang City. The study employed analytical correlative design with cross-sectional approach. The population of the study was all pregnant women from the 1stto 3rd trimester who visited the Obstetrics and Gyneclogy Polyclinic at S.K.Lerik General Hospital, Kupang City. There were106 respondents recruited as the sample through purposive sampling technique. The data were collected using questionnaire and analysed by using Spearman Rho test analysis. The findings showed that there was significant correlation between knowledge and attitudes which obtained ρ value 0.015, with correlation coefficient of 0.236. This meant that there was weak and positive correlation between the variables. The analysis between knowledge and utilization of KIA book obtained ρ value 0.593, it was insignificant because 0.05. Furthermore, there was significant correlation between attitudes and utilization of KIA book which obtained ρ value 0.000 with a correlation coefficient of 0.494. This meant that there were moderate positive correlation between the variables. The higher the knowledge of pregnant women, the better the attitude of pregnant women towards the utilization of KIA book, and the higher the attitude of pregnant women, the better they are in utilizing KIA book. Meanwhile, knowledge does not affect pregnant women in utilizing KIA books. Keywords: Knowledge, Attitude, Utilization of KIA Books. ABSTRAK Penyulit atau komplikasi yang terjadi pada masa kehamilan dapat dicegah dengan mengetahui tanda bahaya selama kehamilan. Salah satu cara mengetahui tanda bahaya kehamilan yaitu dengan memanfaatkan buku KIA. Rendahnya pengetahuan ibu hamil tentang tanda bahaya dapat menyebabkan meningkatnya Angka Kematian Ibu. Mengetahui Hubungan Pengetahuan dan Sikap Ibu Hamil Tentang Tanda Bahaya Kehamilan Terhadap Pemanfaatan buku KIA di Poli Kandungan RSUD.S.K.Lerik Kota Kupang. Desain penelitian analitik dengan pendekatan cross sectional. Populasi semua ibu hamil dari trimester 1-3 yang datang berkunjung di Poli Kadungan RSUD S.K.Lerik Kota Kupang dengan jumlah sampel 106 responden. Teknik sampling berupa non probability sampling menggunakan purposive sampling. Alat pengumpulan data berupa kuesioner dengan analisis uji Spearman rho. Analisis hubungan pengetahuan dan sikap didapat 0.015, karena 0.05, maka disebut signifikan, dengan koefisien korelasi 0.236. Artinya, tingkat kekuatan hubungannya lemah dengan arah hubungan kedua variabel tersebut searah. Analisis hubungan antar pengetahuan dan pemanfaatan buku KIA didapat sebesar 0.593, karena 0.05, maka disebut tidak signifikan. Analisis hubungan sikap dan pemanfaatan buku KIA didapat sebesar 0.000, karena 0.05, maka disebut signifikan, dengan koefisien korelasi 0.494. Artinya, tingkat kekuatan hubungannya sedang dengan arah hubungan kedua variabel tersebut searah. Semakin tinggi pengetahuan ibu hamil maka semakin baik sikap ibu hamil terhadap pemanfaatan buku KIA, dan semakin tinggi sikap ibu hamil maka semakin baik dalam memanfaatkan buku KIA, sedangkan pengetahuan tidak mempengaruhi ibu hamil dalam pemanfaatan buku KIA. Kata Kunci: Pengetahuan, Sikap, Pemanfaatan Buku KIA